Skills and dispositions of critical thinking: are they sufficient? - Nieto, Ana María; Sainz, Carlos (Anales de Psicología / Annals of Psychology, 2010)
Traditionally, it has been held that critical thinking requires a set of cognitive skills and dispositions. The present work supports the opinion of some theorists who have proposed that these might not be the only two ingredients necessary for improving critical thinking. More specifically, new factors could be necessary if critical thinking is to be achieved, such as gaining an epistemological understanding of critical thinking; reaching a given level of epistemological development, or the beliefs that are held about thinking. These new components are analysed conceptually and instructionally. Special attention is also devoted to dispositions.